The influence of team social media usage on individual knowledge sharing and job performance from a cross-level perspective. Issue 5 (11th October 2019) - Cui, Xiling; Huo, Baofeng; Lei, Yang; Zhou, Qiang
Abstract : Purpose: The purpose of this paper is to examine how team social media usage (SMU) affects two types of knowledge sharing (KS), namely, in-role and extra-role KS, and then individual job performance. The study also examines the mediating effects of two types of KS and the main and moderating effects of team performance norms on individual job performance. Design/methodology/approach: This study applies the theory of communication visibility to develop a cross-level model and then validate it through a three-wave survey from 600 individuals in 120 teams. Hierarchical linear model is used to test the hypotheses. Findings: The results suggest that team SMU improves team members' in-role and extra-role KS, and thus enhances their individual job performance. The in-role and extra-role KS have partial mediating effects between team SMU and job performance. The results also show that team performance norms have a positive main effect on individual job performance, but negatively moderate the relationship between individual extra-role KS and job performance. Research limitations/implications: This study contributes to the operations management literature by examining the effects of team SMU from a multilevel perspective. Practical implications: The findings provide managers with ways to improve individual KS and job performance. Originality/value: This study is one of the first to investigate the effects of team SMU on individual KS and job performance. It also identifies the two-sided effects of team performance norms.